Analisis Rasio Likuiditas dan Profitabilitas untuk Menilai Kinerja Keuangan Perusahaan pada PT. Astra International Tbk - Maheni Damanik; Wahyul Wahyul (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this research was to know the financial performance of PT. Astra International Tbk based on liquidity and profitability ratios. The research used qualitative descriptive methods, where data collections methods from of library methods, with secondary data types and internal and external data sources. Results showed that of financial statement analysis used liquidity ratios, namely Current Ratio, Quick Ratio and Cash Ratio were not good because it has decreased every years, although still the ability to pay current debt but would have a bad effect if this decline was not overcome well. Financial performance in terms of profitability ratios namely Gross Profit Margin, Net Profit Margin, Return on Assets and Return on Equity were in good condition in produce profits and has increase every years.